Fremdenverkehrswirtschaftliche Entwicklung und Arbeiterwanderungen in Kenya.: Das Beispiel der Küstenzone - Vorlaufer, Klaus (ERDKUNDE, 1979)
The development of tourist centres in the coastal zone of Kenya is connected with the intensive influx of labour from other parts of the country. The majority of hotel employees are provided by this labour. A greater involvement of local labour in tourism has therefore probably not taken place because the coastal population shows only relatively slight inclination towards social mobility as a result of specific socio-economic characteristics (moslems, limited education). However, for the majority of immigrants the tourist economy does not present the immediate pull factor. It is rather the search for general work opportunities that predominantly decides emigration, which is first of all largely directed to the towns of Mombasa and Malindi with their larger labour market. For most people the change from traditional ways of life to the tourist industry took place in social and spatial stages. In this different patterns of step-wise migration have been established for different peoples in Kenya. On the whole labour migrations directed towards the centres of tourism follow to a large degree the currents of migration typical for Kenya generally. Tourism did not in principle connect new emigration regions to its centres. A major problem, however, is the great number of family separations, for the majority of married immigrants live at the place of work without their families. This fact helps to maintain the close bonds between regions of emigration and immigration.